Iridoids derived from Valeriana jatamansi Jones alleviates neuroinflammation and blood spinal cord barrier permeability after spinal cord injury by activating the Nrf2/HO-1 signaling pathway - He, Yongzhi; Lu, Jiachun; Pang, Rizhao; Ding, Lijuan; Wang, Yunyun; Xiao, Hua; Cheng, Chao; Luo, Yushan; Hu, Xiaoming; Wang, Wenchun (Frontiers in Pharmacology, 2025)
BackgroundValeriana jatamansi Jones, a globally utilized medicinal plant, exhibits favorable pharmacological effects against depression and tumors. Iridoids derived from V. jatamansi (IRFV) promote recovery following spinal cord injury (SCI). Inflammation and disruption of the blood-spinal cord barrier (BSCB) represent key pathological processes in SCI. However, the specific effects of IRFV on neuroinflammation and BSCB integrity remain unexplored.Methods and ResultsThis study aims to elucidate the functional significance and molecular mechanisms by which IRFV modulates neuroinflammation and preserves BSCB function following SCI. Experimental results demonstrated that IRFV treatment significantly enhanced locomotor recovery in SCI models. Moreover, IRFV reduced macrophage infiltration and inhibited inflammatory mediator secretion, effectively attenuating the neuroinflammatory response. IRFV also mitigated BSCB permeability alterations by suppressing tight junction disruption and structural damage. In vitro experiments revealed that IRFV attenuated oxygen-glucose deprivation/reperfusion (OGD/R)-induced endothelial cell damage and tight junction protein degradation, suggesting a potential mechanism for its BSCB protection. Critically, the protective effects of IRFV were abolished upon suppression of the Nrf2/HO-1 pathway, demonstrating its essential role in this process.ConclusionIn conclusion, our study demonstrates that IRFV treatment activates the Nrf2/HO-1 signaling pathway, thereby suppressing neuroinflammation, mitigating blood-spinal cord barrier damage, and promoting recovery from SCI, thus highlighting its therapeutic potential.